DEPENDENCE OF THE AMOUNT OF EMISSIONS FROM THE SOLID FUEL COMPOSITION - Рындюк, Дмитрий; Шелеш, Татьяна; Беднарская, Инна; Беднарская, Яна; Качкивский, Денис (SWorldJournal, 2020)
The main task of this study is to determine the quantitative characteristics of harmful emissions into the atmosphere depending on the composition of solid fuels. The study calculated the emission of carbon oxides and nitrogen, sulfur dioxide and particu